Retreat dribble and tight zig-zag combo training: does it affect the improvement of basketball athletes' dribble skills? - Pelamonia, Shandy Pieter; Puriana, Ramadhany Hananto (Universitas Tanjungpura, 2023)
Background and Study Aim. Basketball is one type of sport that is often played by the community, especially among students. In the game of basketball, effective and efficient movements need to be based on the mastery of good basic technical skills. The purpose of this study is to determine the effect of retreat dibble and tight zig-zag combos on improving dribbling to support techniques that aim to get points for basketball athletes.Material and Methods. This study uses a